(untitled) (Rudarsko-geološko-naftni zbornik, 2018)
A simulation model of the slim-tube test has been developed to validate the laboratory experiment and used EOS as well as to investigate the possibility of serving as a fast and reliable tool for MMP determination. Sensitivity analyses were performed by testing different grid block sizes (different number of cells), changing Corey’s coefficients for relative permeability curves, varying flow rates and PVT models. Minimum miscibility pressure from the simulation model is estimated as the intersection of the two different trend line curves of oil recoveries versus the injected volume of CO2. The oil recoveries were underestimated by numerical simulation on a basic case model. This is related to the usage of single “X shaped” relative permeability curves in all simulation cases, i.e. for immiscible, near miscible and miscible conditions. In addition, by fine tuning binary interaction parameters in equation of state model and introducing different relative permeability curves for immiscible and near miscible cases, better matching of slim-tube simulation can be achieved.